Genetic evaluation of the performance of malaria parasite clearance rate metrics. - Nkhoma, S; Stepniewska, K; Nair, S; Phyo, A; Mcgready, R; Nosten, F; Anderson, T (2013)
Accurate measurement of malaria parasite clearance rates (CRs) following artemisinin (ART) treatment is critical for resistance surveillance and research, and various CR metrics are currently used. We measured 13 CR metrics in 1472 ART-treated hyperparasitemia infections for which 6-hour parasite counts and parasite genotypes (93 single nucleotide polymorphisms [SNPs]) were available. We used heritability to evaluate the performance of each metric. Heritability ranged from 0.06 ± 0.06 (SD) for 50% parasite clearance times to 0.67 ± 0.04 (SD) for clearance half-lives estimated from 6-hour parasite counts. These results identify the measures that should be avoided and show that reliable clearance measures can be obtained with abbreviated monitoring protocols.